La Biblioteca Nacional. - Guerra García, Gema; Cano Riofrío, Cristina; Rubalcaba Blanco, Raúl; Redondo Morales, Esperanza; Benito Sanz, Raquel (Documentación de las Ciencias de la Información, 1998)
Sin resumen